Rapid facial cryotherapy for combat sports: A comparison of materials and methods for cooling facial tissues in 60 seconds or less - Beauregard, T. A.; Vaile, J.; Whitney, L.; Merrick, M.; Moody, V. (Journal of Sport Rehabilitation, 2020)
Context: Athletes in combat sports who have sustained facial hematomas during competition have traditionally been treated with an enswell. These treatments take place between rounds of the competition and generally last less than 60 seconds. The efficacy of this modality has not been studied. Other modalities may provide a more effective cryotherapy treatment in this timeframe. Objective: To compare the efficacy of different forms of rapid cryotherapy to cause surface temperature changes of the face within 60 seconds of application. Design: Crossover study. Setting: Laboratory. Participants: Eleven healthy men (age 21.73 [1.42] y, mass 82.1 [5.6] kg, heigh 177.2 [7.0] cm). Interventions: A 60-second treatment using chilled surgical steel enswell, copper, commercial cold pack, aluminum, brass, ice cube, ice pack, and saltwater pack. Main Outcome Measures: Preintervention and postintervention surface facial temperatures. Results: The ice bag, cold pack, ice cube, saltwater pack, and stainless-steel enswell caused statistically different temperatures preintervention to postintervention. The ice bag and saltwater pack cause statistically greater cooling than the other materials tested. Conclusions: This study does not support the clinical use of an enswell to provide short-duration cryotherapy treatments to facial tissue, as ice packs are more effective.